Ferromagnetic resonance investigations of cobalt-implanted polyimides - Rameev, B; Okay, C; Yildiz, F; Khaibullin, RI; Popok, VN; Aktas, B (Elsevier, 2004)
Co+ ions of 40keV were implanted in thin polyimide foils with doses in the range of (0.25-1.50) x 10(17) ions/cm(2) at ion current densities of 4, 8 and 12muA/cm(2). The cobalt-implanted polymer foils were annealed at a temperature of 300degreesC for 2h in vacuum. Both the as-implanted and post-annealed samples were investigated by the ferromagnetic resonance (FMR) technique supplemented by transmission electron microscopy (TEM). TEM investigations showed that the implantation results in the formation of cobalt granules in the irradiated polymer layer with the thickness of about 70 nm. The mean lateral size of cobalt granules varied within 5-20 nm depending on the dose. The annealing of the implanted samples induced coalescence of the cobalt granules and increase of their lateral sizes. No FMR signals were found for the as-prepared polymer foils implanted by cobalt ions at low current density of 4 muA/cm(2). FMR signals were observed for the as-prepared samples implanted at higher ion current densities of 8 and 12 muA/cm(2) as well as for all annealed samples. The values of the effective magnetisation were extracted from the FMR spectra measured at different sample orientations in the applied magnetic field. Dose dependencies of the FMR absorption intensity and effective magnetisation were obtained for the annealed films. The magnetic properties of the synthesised cobalt-polymer composite materials and their modification due to the annealing treatment are discussed. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: ion implantation; granular magnetic films; ferromagnetic resonance